2018
DOI: 10.1007/s00380-018-1187-4
|View full text |Cite
|
Sign up to set email alerts
|

Aortic elasticity deterioration proves intrinsic abnormality of the ascending aorta in pediatric Turner syndrome unrelated to the aortic valve morphology

Abstract: Turner syndrome (TS) is a common genetic disorder in females with high incidence of ascending aortic dilatation and even dissection occurring as early as in the second decade. Known risk factors (RF) are bicuspid aortic valves (BAV), coarctation of the aorta (CoA), and arterial hypertension. Since 10% of dissections occur in patients without RF, an intrinsic aortic wall abnormality has been postulated. This study aimed to investigate the elasticity of the ascending aorta as a surrogate marker of aortic wall te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 38 publications
0
12
0
1
Order By: Relevance
“…Coarctation is associated with an increased likelihood of aortic dilation and dissection (Bambul Heck, Pabst von Ohain, Kaemmerer, Ewert, & Hager, ; Cools, Brown, & Gewillig, ; Eckhauser et al, ). Hypertension, a common consequence of aortic coarctation that may manifest in childhood, and altered compliance or distensibility of the aorta, which is prevalent in patients with coarctation, may both contribute to aortic disease (Hjerrild et al, ; Pees et al, ; Schoepp et al, ; Wen et al, ). Re‐interventions due to re‐coarctation are often necessary in adulthood.…”
Section: Cardiovascular Health Issuesmentioning
confidence: 99%
“…Coarctation is associated with an increased likelihood of aortic dilation and dissection (Bambul Heck, Pabst von Ohain, Kaemmerer, Ewert, & Hager, ; Cools, Brown, & Gewillig, ; Eckhauser et al, ). Hypertension, a common consequence of aortic coarctation that may manifest in childhood, and altered compliance or distensibility of the aorta, which is prevalent in patients with coarctation, may both contribute to aortic disease (Hjerrild et al, ; Pees et al, ; Schoepp et al, ; Wen et al, ). Re‐interventions due to re‐coarctation are often necessary in adulthood.…”
Section: Cardiovascular Health Issuesmentioning
confidence: 99%
“…Previous studies have evaluated the impairment in ascending aortic elastic properties in different diseases using different techniques to analyze the above elastic parameters. 13 18 Although many studies 19,20 analyzed the prevalence of aortic stiffness in either hypertensive and diabetic patients, only few were conducted to investigate whether essential hypertension (EH) or type 2 diabetes mellitus (T2DM) had a greater effect on aortic stiffness in patients with T2DM + EH.…”
Section: Introductionmentioning
confidence: 99%
“…Others have also investigated whether the presence of BAV can explain the increased aortic stiffness in patients with TS but the results are contradictory. Two studies 8 23 showed reduced ascending aortic distensibility and increased AA-PWV independently of the presence of BAV, while Devos et al 9 showed that only patients with BAV have a reduced ascending aortic distensibility. Our results are more in line with the first study, since we found no effect of BAV on stiffness.…”
Section: Discussionmentioning
confidence: 99%